عمل ما يلي


3x + 21 = 3x + 3 \times 7 = 3(x + 7)

 4x - x^2 = x(4 - x)

 -5x + 20 = -5x + 5 \times 4 = 5(-x + 4)

 5x^2 - 8x = x(5x - 8)

(x - 1)(2x + 3) - (x - 1)(2 - x) = (x - 1)[(2x + 3) - (2 - x)] =  (x - 1)(2x + 3 - 2 + x) = (x - 1)(3x + 1)

 (2x + 1)^2 + (2x + 1)(x + 3) = (2x + 1)[(2x + 1) + (x + 3)] =  (2x + 1)(2x + 1 + x + 3) = (2x + 1)(3x + 4)

 (5x - 2)(2x + 7) - (5x - 2) = (5x - 2)[(2x + 7) - 1] =  (5x - 2)(2x + 6) = 2(5x - 2)(x + 3)

Welcome To My Website
hassan.ab.ma © 2017.Free Web Site